The Boundaries of Ethics – Art without Boundaries - Hiltrud Schinzel (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Interdisciplinary knowledge exchange and new techniques as well as general technical and environmental developments prompt to review conservation ethics. Contemporary artworks show the state of the now in a paradigmatically aesthetic way which is documented by some examples and quotes. Findings in the sciences and humanities – neurosciences in focus – are named concerning the perception of art by the protagonists: artist, conservator, art-teacher/promoter and viewer. They document that it is relevant to modify conservation’s function according to human biological conditions including basic human needs. Some topical aspects are described paradigmatically by some characteristics of the material wood and its artistic use in different cultural and temporal settings. Wood - as any material presented by cultural artefacts - transports aesthetic knowledge that can stimulate and foster awareness and empathy, e.g. now, while climate changes, concerning nature.